Modification of surface properties of Ti-16Si-4B powder alloy by plasma immersion ion implantation - Fernandes, Bruno Bacci; Ueda, Mario; Mello, Carina Barros; Fernandes, Paulino Bacci; Reuther, Helfriecl; Ramos, Alfeu Saraiva [UNESP] (Elsevier B.V., 2011)
Results of the surface modification of Ti-16Si-4B powder alloy by nitrogen ion implantation are presented, together with the experimental description of the preparation of that powder by high-energy ball milling and hot pressing. The phase structure, chemical composition and morphology of sample surfaces were observed by utilizing X-ray diffractometer (XRD), atomic force microscope (AFM) and scanning electron microscopy (SEM). A tribological characterization was carried out with a ball-on-disc tribometer and an SEM. Friction coefficient is compared with the one obtained for Ti-6Al-4V alloy and the wear scars characterized by SEM/EDS (energy dispersive spectroscopy). The concentration profile of the detected elements have been investigated using Auger electron spectroscopy (AES) depth profiling. Our results show that a shallow implanted layer of oxygen and nitrogen ions were obtained at the Ti-16Si -4B alloy surface, sufficient to modify slightly its tribological properties. Crown Copyright (C) 2011 Published by Elsevier Ltd. All rights reserved.
Keywords: Multiphase intermetallics; Tribological properties; Powder metallurgy